Magneto-transport properties of B-, Si- and N-doped graphene. (30th April 2020) - Shih, Po-Hsin; Do, Thi-Nga; Gumbs, Godfrey; Huang, Danhong; Pham, Thanh Phong; Lin, Ming-Fa
Abstract: The effect due to doping by B, Si, N atoms on the magneto-transport properties of graphene is investigated using the generalized tight-binding model in conjunction with the Kubo formula. The crucial electronic and transport properties are greatly diversified by different types of dopant and doping concentrations. The effect of these guest atoms includes opening a band gap, thereby giving rise to rich Landau level energy spectra and consequently a unique quantum-Hall conductivity. The Fermi-energy dependent quantum-Hall effect appears as a step structure having both integer and half-integer plateaus. Doping with Si leads to an occurrence of a zero quantum-Hall conductivity, unlike the plateau sequence for pristine graphene. The predicted dopant- and concentration-enriched quantum-Hall effect for doped graphene can provide useful information for magneto-transport measurements, possible technological and even metrology applications. Graphical abstract: Image 1